Pengaruh Literasi Keuangan dan Gaya Hidup Modern Terhadap Perilaku Konsumtif Mahasiswa di Yogyakarta - Wahyuni, Yuyun; Cahyaningrum, Rahmawati (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
The purpose of this study was to determine the significant influence of financial literacy and lifestyle on consumer behavior among students in Yogyakarta. The population in this study were active students in Yogyakarta. The sampling method used was purposive sampling, with the criteria being that respondents were still registered as active students and resided in Yogyakarta. A sample of 200 respondents was selected. The research instrument used validity and reliability tests. Data analysis used multiple linear regression. Hypothesis testing used t-tests and F-tests. The results showed that financial literacy had a negative and significant influence on consumer behavior. Meanwhile, lifestyle variables had a positive and significant influence on consumer behavior. This suggests that students who understand financial literacy will not engage in consumer behavior. Meanwhile, students with a modern lifestyle will engage in consumer behavior.